Conduction delays across the specialized conduction system of the heart: Revisiting atrioventricular node (AVN) and Purkinje-ventricular junction (PVJ) delays - Choi, Bum-Rak; Ziv, Ohad; Salama, Guy (Frontiers in Cardiovascular Medicine, 2023)
Background and Significance: The specialized conduction system (SCS) of the heart was extensively studied to understand the synchronization of atrial and ventricular contractions, the large atrial to His bundle (A-H) delay through the atrioventricular node (AVN), and delays between Purkinje (P) and ventricular (V) depolarization at distinct junctions (J), PVJs. Here, we use optical mapping of perfused rabbit hearts to revisit the mechanism that explains A-H delay and the role of a passive electrotonic step-delay at the boundary between atria and the AVN. We further visualize how the P anatomy controls papillary activation and valve closure before ventricular activation. Methods: Rabbit hearts were perfused with a bolus (100-200µl) of a voltage-sensitive dye (di4ANEPPS), blebbistatin (10-20µM for 20 min) then the right atrial appendage and ventricular free-wall were cut to expose the AVN, P fibers (PFs), the septum, papillary muscles, and the endocardium. Fluorescence images were focused on a CMOS camera (SciMedia) captured at 1K-5K frames/s from 100x100 pixels. Results: AP propagation across the AVN-His (A-H) exhibits distinct patterns of delay and conduction blocks during S1-S2 stimulation. Refractory periods were 81±9, 90±21, 185±15 ms for Atrial, AVN, and His, respectively. A large delay (>40 ms) occurs between atrial and AVN activation that increased during rapid atrial pacing contributing to the development of Wenckebach periodicity followed by delays within the AVN through slow or blocked conduction. The temporal resolution of the camera allowed us to identify PVJs by detecting doublets of AP upstrokes. PVJ delays were heterogeneous, fastest in PVJ that immediately trigger ventricular APs (3.4±0.8 ms) and slow in regions where PF appear insulated from the neighboring ventricular myocytes (7.8±2.4 ms). Insulated PF along papillary muscles conducted APs (>2 m/s), then triggered papillary muscle APs (<1 m/s), followed by APs firing of septum and endocardium. The anatomy of PFs and PVJs produced activation patterns that control the sequence of contractions ensuring that papillary contractions close the tricuspid valve 2-3 ms before right ventricular contractions. Conclusions: The specialized conduction system can be accessed optically to investigate the electrical properties of the AVN, PVJ and activation patterns in physiological and pathological conditions.